THE DIFFICULTIES FACED BY MICRO AND SMALL ENTERPRISES IN THE FORMAL MARKET ACCESS: THE CASE IN SMALL AND MICRO ENTERPRISES IN THE CITIES OF MAKASSAR AND KABUPATEN GOWA SOUTH SULAWESI - Rahman, Zainuddin (Journal of Humanity, 2016)
This research aims to analyze about the difficulties faced by micro and smallenterprises in accessing markets in sustaining and expanding the operation and the survivalof their businesses. Samples taken from the 45 micro and small businesses (UMK) chosendeliberately from the entire population. Design research in the applied ResearchExploratory. Data collection is done with in depth interviews with business owners(industry) to obtain data that is associated with this research. From a sample of researchfound that very few micro and small businesses (UMK) managed to access the formalmarket, the main reason is the inability of their products to meet the requirements set bythe institution of a formal marketing, they are only able to do marketing. The conclusionsof the research are: a). skills principals UMK on marketing management are generally verylow, b). quality of the resulting product is still low so as to make their difficulties indealing with competitors in the market, c) continuity in serving customers/partner has yetto be secured, d) difficulty in using modern production technology, because of lack ofcapital, e) slow in doing the response to changes in the market. Recommended: that theGovernment should also play a more active role in facilitating the ease of access to theformal market, by helping UMK in partnerships, and the provision of facilities for productmarket UMK on any area in the form of marketing outlets adopted the model AlphaMarch.